Участь місцевого компонента у формуванні зарубинецької культури - Пачкова, С.П. (Археологія, 1999)
Час формування зарубинецької культури найбільш об'єктивно визначається хронологією уламків античних амфор із зарубинецьких поселень. Участь автохтонного населення у створенні зарубинецької культури виявляється не тільки і не стільки в наявності елементів попередніх культур, скільки у спроможності створити нову культуру, відмінну як від попередніх місцевих, так і від привнесених ззовні. Начало зарубинецкой культуры по материалам поселений определяется обломками античных амфор с клеймами, наиболее ранние из которых датируются 30—20 гг. III в. до н. э. Согласно современной хронологии среднелатенских фибул, примерно к этому же времени относятся и первые погребения на могильниках. Анализ датирующих вещей местных культур (скифской лесостепной, милоградской и поморской), которые предшествовали зарубинецкой, показывает на резкое прекращение поступления на них латенского импорта в начале III в. до н. э. Это может свидетельствовать про нестабильность жизни племен этих регионов, но не про уход всего населения с этих территорий и про конец функционирования самих культур. Типологическая преемственность в артефактах между предшествующими местными культурами и зарубинецкой, говорит об определенном вкладе первых при формировании зарубинецкой культуры. Влияние каждой из местных культур было различным по значимости, но наиболее ощутимо именно на своей территории. И все же поморский компонент ощутимый во всех регионах зарубинецкой культуры, хотя субстратом он являлся только для части Припятского Полесья и полностью пришлым для территории Поднепровья. Роль автохтонного населения проявляется также и в том, что зарубинецкая культура является новой синтезированной и синкретической, которая не повторяет и не продолжает предшествующие и не копирует ни одну из привнесенных извне. Given the materials from the settlements, one can attribute the beginning of the Zarubyntsi Culture by the fragments of the antique amphorae with stamps; the earliest fragments are datable to the 30-20s of the third century BC, According to modem chronology of the Middle Laten fibulae, the first burials on the Culture’s burial mounds date from the same period. The analysis of datable materials of the local cultures (Forest Steppe Scythian, Mylohrad and Pomorie) - predecessors of the Zarubyntsi Culture - shows the cessation of supplies of the Laten imports at the beginning of the third century BC. Conceivably, the cessation may be attributed to the vulnerable positions of the tribes in these regions rather than the depopulation of the territories or disappearance of the cultures. Typological continuity of the artifacts the Zarubyntsi Culture and its local predecessors says that they later contributed to the formation of the Zarubyntsi Culture. The impacts differed from culture to culture and were most pronounced at the native territory of each culture. Nevertheless, the component of the Pomorie Culture is pronounced throughout the regions of the Zarubyntsi Culture, although it had only been a substrate partially for Prypiat Polissia and formed a fully arrived component for the Dnieper regions. The role of the autochthon population manifested itself in the fact that the Zarubyntsi Culture became a new synthetic and syncretic culture that was not a copy of its predecessor, nor it continued the traditions of the predecessors.